LINGUISTIC ANALYSIS OF LEXICAL UNITS IN ENGLISH AND UZBEK RELATED TO THE CONSTRUCTION INDUSTRY (Scientific journal of the Fergana State University, 2026)
This article provides a linguistic and semantic analysis of lexical units related to the construction of buildings and structures in English and Uzbek. It explores the development of construction-related terminology, its origins in common language, its role in international terminology, and its formation as scientific and technical lexical units. Based on theoretical views of prominent linguists, the classification of lexical units and their semantic transformations are discussed with relevant examples.